Нова продукція pcbn – свердла з двошарового композита кубічного нітриду бору - Беженар, М.П.; Шульженко, О.О.; Боженок, В.М.; Божко, С.А.; Нагорний, П.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
It is developed new PCBN – a two-layer composite of cubic boron nitride with a substrate of
cemented carbide. Properties of a working layer a composite – high hardness, fracture strength and an electrical conductivity in a combination to necessary geometry sintered in HPA preparations, have provided manufacturing of complex contour profile the tool.